An Examination of the Techno-Economic Viability of Hybrid Grid-Integrated and Stand-Alone Generation Systems for an Indian Tea Plant - Thirunavukkarasu, M.; Sawle, Yashwant (Frontiers in Energy Research, 2022)
Tea factories throughout the globe have problems in working with sustainability and in terms of product costs are competitive. All tea plants in India rely on the national grid for their electrical needs and diesel for their thermal energy and transportation, which are encountering high costs, high emissions, and issues of accessibility. The shortages of fossil fuels, especially coal, and technical losses lead to a lack of electricity, and suffering from unreliable supply creates a great strain on utilizing India's national grid.The aim of this paper is to analyze off-grid and on-grid based hybrid renewable systems to meet the energy demands of a tea factory in India. By utilizing hydro energy combined with solar and biomass energy, a HOMER-based optimization model has been developed to meet the requirements of thermal, power, and hydrogen with the aim of minimizing the cost of energy (Electrical and Hydrogen). In this tri-generation system, utilizing excess renewable power and waste heat recovery options are employed to generate thermal power, which ultimately reduces the fuel consumption of the boiler and emissions. The findings show that recovering excess electricity and waste heat would increase renewable fraction, decrease the energy cost and emissions from the system, emphasizing the importance of TLC and CHP in HRES. The results show that in both off-grid and on-grid systems, the PV/Biomass-CHP/Hydro/TLC microgrid systems have achieved the least NPC of 1.75 M and -10.5 M respectively. The Levelized cost of hydrogen for the grid integrated solar/biomass-CHP/hydro/TLC hybrid system is predicted to be a minimum of -64.5 /kg. In accordance with the results of the simulation, the grid-connected system is the most cost-effective than a stand-alone system due to the revenue obtained from selling renewable power to the grid.